Phase Transitions in Multicomponent Media at Low Temperatures - Vozovik , Kristina; Chernobai , Nadiia; Kadnikova, Nataliya (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 294